Redesigning Enzymes for Biocatalysis: Exploiting Structural Understanding for Improved Selectivity - Ding, Yaoyu; Perez-Ortiz, Gustavo; Peate, Jessica; Barry, Sarah M. (Frontiers in Molecular Biosciences, 2022)
The discovery of new enzymes, alongside the push to make chemical processes more sustainable, has resulted in increased industrial interest in the use of biocatalytic processes to produce high value and chiral precursor chemicals. Huge strides in protein engineering methodology and in silico tools have facilitated significant progress in the discovery and production of enzymes for biocatalytic processes. However, there are significant gaps in our knowledge of the relationship between enzyme structure and function. This has demonstrated the need for improved computational methods to model mechanisms and understand structure dynamics. Here we explore efforts to rationally modify enzymes towards changing aspects of their catalysed chemistry. We highlight examples of enzymes where links between enzyme function and structure have been made, thus enabling rational changes to the enzyme structure to give predictable chemical outcomes. We look at future directions the field could take and the technologies that will enable it.